2009
DOI: 10.1007/s10974-010-9202-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term gravitational unloading on rat and mongolian gerbil muscles

Abstract: Gravitational unloading leads to destructive changes in the structure and function of muscle fibers. However, the role of the EMG activity level is still unclear. We measured changes caused by one- and three-day hypogravity in the following muscles: Soleus (Sol), Tibialis anterior (TA) and Gastrocnemius c.m. (MG). We used Wistar rats and Mongolian gerbils. The following parameters were assessed: the specific force of contraction of isolated fibers by tensometry, the transverse stiffness of the contractile appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Our results on the relative content of desmin in functional unloading are consistent with the data described earlier [9,10]. In addition, the authors of [5] showed that, after gravitational unloading, the content of desmin in the rat vastus muscle decreased in the first day of suspending, remained below the control after 3 days, and almost completely restored on day 9.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results on the relative content of desmin in functional unloading are consistent with the data described earlier [9,10]. In addition, the authors of [5] showed that, after gravitational unloading, the content of desmin in the rat vastus muscle decreased in the first day of suspending, remained below the control after 3 days, and almost completely restored on day 9.…”
Section: Discussionsupporting
confidence: 92%
“…Atrophy development is associated with degradation of cytosk eletal proteins, which is apparently induced by an increase in the concentration of calcium ions [6,9] and subsequent activation of calcium dependent pro teases calpains [5]. Substrates of the calpain pro teolytic system are important cytoskeletal proteins desmin and α actinin 2 [5].…”
mentioning
confidence: 99%
“…Changes in the structure of muscle fibers, observed in a gravity disuse and follow-up readaptation period, naturally lead to a change in mechanical properties that depend on the integrity of the structure, such as stiffness. In turn, changes in the longitudinal and transversal stiffness are directly related to the changes in contractile properties of muscle fibers [12, 22, 23]. The results of the study of transversal stiffness of contractile apparatus suggest that gravitational unloading caused different changes in slow and fast muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Structural basis of the transversal stiffness of the sarcolemma with cortical cytoskeleton is a network of filaments formed by nonmuscle actin-beta-actin. To form such a network, a host of capping proteins is needed, one of which is alpha-actinin-4, attention to which in a gravity disuse is due primarily to the fact that its binding to beta-actin depends on the content of calcium ions, the increase of which in these conditions has been shown previously [22, 24, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…Those muscles with functional parameters, which deviated by Ͼ50% from the regression line, were also differentiated during the histological analysis. The agreement between functional and histological analysis demonstrates that the in situ assay system accurately reflects muscle functionality (24,27,40,44).…”
Section: Discussionmentioning
confidence: 74%